Discovery Learning Model Assisted by Google Classroom and Zoom Efforts to Improve Critical Thinking Ability of Geography Education Students - Risky Amelia; Bahtiar; Ramdani Salam; Vrita Tri Aryuni (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2021)
The purpose of this study was to determine the effect of the Discovery Learning model assisted by Google Classroom and zoom in the Environmental Education course on the critical thinking skills of Khairun University Geography Education students. The research approach used was a quasi experimental design with a pretest-posttest control group experimental design. Data analysis with parametic statistics for hypothesis testing, namely covariance analysis (Ancova) using SPSS 22 for windows with a significance level of 0.05. The research was carried out in the Geography Education Study Program, Khairun University with student respondents who contracted the Environmental Education course. The results of this study indicate that there is a difference in the effect of learning between discovery learning and conventional models that both use google classroom and zoom on students' critical thinking skills with the Sig. 0.00.